Epidemiology of hand and wrist injuries in sports - Leyes, M. (1998)
Incidence Mechanisms of injury to the wrist in sports Tendinitis and tenosynovitis of the hand and wrist Closed tendon injuries of the hand Ligamentous injuries of the wrist in the athlete Ligamentous injuries of the fingers Other Soft Tissue Lesions of the Wrist Wrist fractures Metacarpal and phalangeal fractures in athletes Entrapment neuropathies Vascular injury Protective splinting of the hand Forearm injuries Osseous injuries Entrapment neuropathies